2012
DOI: 10.1007/s12020-012-9835-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of adrenal insufficiency: an update

Abstract: Adrenal insufficiency may be caused by the destruction or altered function of the adrenal gland with a primary deficit in cortisol secretion (primary adrenal insufficiency) or by hypothalamic-pituitary pathologies determining a deficit of ACTH (secondary adrenal insufficiency). The clinical picture is determined by the glucocorticoid deficit, which may in some conditions be accompanied by a deficit of mineralcorticoids and adrenal androgens. The substitutive treatment is aimed at reducing the signs and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 157 publications
0
33
0
4
Order By: Relevance
“…Indeed, traditional synthetic glucocorticoids did not fully mimic physiological circadian cortisol rhythm, as serum cortisol levels were abundantly above the expected physiological levels right after tablet intake, with a rapid decrease in the following hours, often reaching undetectable levels [4,15].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, traditional synthetic glucocorticoids did not fully mimic physiological circadian cortisol rhythm, as serum cortisol levels were abundantly above the expected physiological levels right after tablet intake, with a rapid decrease in the following hours, often reaching undetectable levels [4,15].…”
Section: Discussionmentioning
confidence: 99%
“…Doubling or tripling of the daily dose, depending on the degree of stress, is recommended. 70 Subjective health status was significantly reduced compared with sex-and age-matched controls in a cross-sectional study of a large cohort of 427 patients with PAI (n = 232) or SAI (n = 195) in Germany, irrespective of whether individuals were treated with hydrocortisone, prednisolone or cortisone acetate. 71 A subsequent cross-sectional study of patients with PAI (n = 194) or SAI (n = 140) showed that those receiving daily doses of hydrocortisone of 30 mg or higher had significantly (P < 0Á05) impaired subjective health status according to two of eight dimensions of the Short-Form 36 health questionnaire ('general health perceptions' and 'role functioning physical') and in three of five Giessen Subjective Complaints List-24 scales ('gastric', 'heart' and 'global symptom' scores) compared with those receiving lower hydrocortisone doses.…”
Section: Effects Of Glucocorticoid Dosing Regimensmentioning
confidence: 97%
“…The glucocorticoid doses should be increased in stressful situations, such as high body temperature, trauma, surgery and during any intercurrent illness. Doubling or tripling of the daily dose, depending on the degree of stress, is recommended …”
Section: Effects Of Glucocorticoid Dosing Regimensmentioning
confidence: 99%
“…It consists mainly in supplementing the deficient glucocorticoids and mineralocorticoids, which brings about a prompt and spectacular improvement [11, 12]. However, the lack of the proper diagnosis of adrenal insufficiency can have tragic sequel since this pathology leads to adrenal crisis and, if not treated with parenterally administered glucocorticoids, is lethal.…”
Section: Discussionmentioning
confidence: 99%